Percutaneous Decommissioning 11 Years After Initial CF-LVAD Placement - Max Ruge, MD; Stefanie Marek-Iannucci, MD, PhD; H. Todd Massey, MD; Nicholas J. Ruggiero, MD; John Lawrence, MD; Praveen Mehrotra, MD; J. Eduardo Rame, MD; Rene Alvarez, MD; Indranee Rajapreyar, MD; Yevgeniy Brailovsky, DO (JACC: Case Reports, 2022)
An 80-year-old man with severe nonischemic cardiomyopathy status post left ventricular assist device (LVAD) placement 11 years prior presented for recurrent LVAD alarms from internal driveline fracture. Given his partial myocardial recovery and his preference to avoid surgical procedures, percutaneous LVAD decommissioning was performed by occlusion of the outflow graft and subsequently driveline removal. (Level of Difficulty: Advanced.)